Cysteine Oxidation within N-terminal Mutant Huntingtin Promotes Oligomerization and Delays Clearance of Soluble Protein - Fox, Jonathan H.; Connor, Teal; Stiles, Megan; Kama, Jibrin; Lu, Zhen; Dorsey, Kathryn; Liebermann, Gregory; Sapp, Ellen; Cherny, Robert A.; Banks, Mary; Volitakis, Irene; DiFiglia, Marian; et al. (The Journal of biological chemistry, 2011)
Huntington disease (HD) is a progressive neurodegenerative disorder caused by expression of polyglutamine-expanded mutant huntingtin protein (mhtt). Most evidence indicates that soluble mhtt species, rather than insoluble aggregates, are the important mediators of HD pathogenesis. However, the differential roles of soluble monomeric and oligomeric mhtt species in HD and the mechanisms of oligomer formation are not yet understood. We have shown previously that copper interacts with and oxidizes the polyglutamine-containing N171 fragment of huntingtin. In this study we report that oxidation-dependent oligomers of huntingtin form spontaneously in cell and mouse HD models. Levels of these species are modulated by copper, hydrogen peroxide, and glutathione. Mutagenesis of all cysteine residues within N171 blocks the formation of these oligomers. In cells, levels of oligomerization-blocked mutant N171 were decreased compared with native N171. We further show that a subset of the oligomerization-blocked form of glutamine-expanded N171 huntingtin is rapidly depleted from the soluble pool compared with “native ” mutant N171. Taken together, our data indicate that huntingtin is subject to specific oxidations that are involved in the formation of stable oligomers and that also delay removal from the soluble pool. These findings show that inhibiting formation of oxidation-dependent huntingtin oligomers, or promoting their dissolution, may have protective effects in HD by decreasing the burden of soluble mutant huntingtin.